2017
DOI: 10.1038/eye.2017.84
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of conditions affecting surgical success of Ahmed glaucoma valve implants in glaucoma secondary to different uveitis etiologies in adults

Abstract: PurposeThere is little known about the long-term efficacy and safety of Ahmed glaucoma valve (AGV) implant and about the conditions affecting surgical success in uveitic glaucoma (UG).Patients and methodsThe charts of adult patients with UG who underwent AGV implantation from 2006 to 2015 were reviewed retrospectively.ResultsData of 46 eyes of 39 patients were evaluated. Mean follow-up was 51.93±23.08 months. Mean preoperative IOP was 37.05±9.62 mm Hg and mean number of preoperative topical anti-glaucomatous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Sungur et al 29 reported the 4-year outcome of AGV in 46 eyes with UG. Most common diagnoses were idiopathic anterior uveitis (17.4%), ankylosing spondylitis (17.4%) Fuchs heterochromic iridocyclitis (17.4%) pars planitis (15.2%) and viral anterior uveitis (10.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sungur et al 29 reported the 4-year outcome of AGV in 46 eyes with UG. Most common diagnoses were idiopathic anterior uveitis (17.4%), ankylosing spondylitis (17.4%) Fuchs heterochromic iridocyclitis (17.4%) pars planitis (15.2%) and viral anterior uveitis (10.9%).…”
Section: Discussionmentioning
confidence: 99%
“…26 These proinflammatory cytokines are thought to lead to a slow remodeling of extracellular matrix over time leading to a higher risk of surgical failure. 19 In previous studies 9,[27][28][29] which evaluated the success of GDD in UG, different courses of uveitis management were used (Table 4). Factors like preoperative initiation of anti-inflammatory agents, route of medications administered, dosage regimen and duration of perioperative treatment were variable.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we performed CPC because of the uncontrolled inflammatory state, which would have jeopardized the performance of any drainage device. 15 Nonetheless, more clinical studies in severe inflammatory diseases are needed to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha reportado en la literatura, como complicaciones de este abordaje: oclusión del tubo, descompensación corneal, diplopía, extrusión del tubo, hipotonía severa, maculopatía hipotónica, desprendimiento de retina, desprendimiento coroideo hemorrágico [3,9,11] .…”
Section: Discussionunclassified